Emergence of Bat-Related Betacoronaviruses: Hazard and Risks - Frutos, Roger; Serra-Cobo, Jordi; Pinault, Lucile; Lopez Roig, Marc; Devaux, Christian A. (Frontiers in Microbiology, 2021)
The current COVID-19 pandemic, with more than 77 million reported cases and 1.700.000 deaths worldwide (mortality rate currently estimated at 2.2%), is a stark reminder that coronaviruses (CoV)-induced diseases remain a major threat to humanity. COVID-19 is only the latest case of betacoronavirus (-CoV) epidemics/pandemics. In the last 20 years, two deadly CoV epidemics, SARS for Severe Acute Respiratory Syndrome (fatality rate 9.6%) and MERS for Middle East Respiratory Syndrome (fatality rate 34.7%), plus the emergence of HCoV-HKU1 which causes the winter common cold (fatality rate 0.5%), were already a source of public health concern. Betacoronaviruses can also be a threat for livestock, as evidenced by the Swine Acute Diarrhea Syndrome (SADS) epizootic in pigs. These repeated outbreaks of -CoV-induced diseases raise the question of the dynamic of propagation of this group of viruses in wildlife and human ecosystems. SARS-CoV, SARS-CoV-2 and HCoV-HKU1 emerged in Asia, strongly suggesting the existence of a regional hot spot for emergence. However, there might be other regional hot spots, as seen with MERS-CoV, which emerged in the Arabian Peninsula. -CoVs responsible for human respiratory infections are closely related to bat-borne viruses. Bats are present worldwide and their level of infection with CoVs is very high on all continents. However, there is as yet no evidence of direct bat-to-human coronavirus infection. Transmission of-CoV to humans is considered to occur accidentally through contact with susceptible intermediate animal species. This zoonotic emergence is a complex process involving not only bats, wildlife and natural ecosystems, but also many anthropogenic and societal aspects. Here, we try to understand why only few hot spots of -CoV emergence have been identified despite worldwide bats and bat-borne -CoV distribution. In this work, we analyze and compare the natural and anthropogenic environments associated with the emergence of -CoV and outline conserved features likely to create favorable conditions for a new epidemic. We suggest monitoring South and East Africa as well as South America as these regions bring together many of the conditions that could make them future hot spots.